MORBIDITY AND MORTALITY IN CHILDREN AND GRANDCHILDREN OF LONG-LIVED SIBLINGS. (11th November 2018) - Christensen, K; Wojczynski, M K; Pedersen, J K; Larsen, L A; Province, M A
Abstract:, Exceptional longevity and disease-free survival are complex phenomena with a known familial component shown to track to the next generation. We combined Danish Civil Registration System and parish birth records to identify 3, 638 long-lived families. Complete pedigrees of 659 families were established and linked to Statistics Denmark. Hospitalizations and mortality in 5, 316 children and 9, 938 grandchildren of the long-lived siblings were compared to 10 age- and sex-matched controls for each child and grandchild. Cox regression analyzes accounted for familial clustering. In both the children and grandchildren generation, we demonstrated substantial lower mortality and risk of hospitalization for virtually all disease groups, most pronounced for the children generation and for tobacco-related conditions and mental disorders. Thus, the health advantage tracks across three generations and future work should focus on identifying the underlying genetic and environmental mechanisms.